Modulation of Zn Ion Toxicity in Pisum sativum L. by Phycoremediation - Zornitsa Karcheva; Zhaneta Georgieva; Svetoslav Anev; Detelina Petrova; Momchil Paunov; Miroslava Zhiponova; Ganka Chaneva (Plants)
Microalgae offer a promising alternative for heavy metal removal, and the search for highly efficient strains is ongoing. This study investigated the potential of two microalgae, Coelastrella sp. BGV (Chlorophyta) and Arthronema africanum Schwabe & Simonsen (Cyanoprokaryota), to bind zinc ions (Zn2⁺) and protect higher plants. Hydroponically grown pea (Pisum sativum L.) seedlings were subjected to ZnSO4 treatment for 7 days in either a nutrient medium (Knop) or a microalgal suspension. The effects of increasing Zn2⁺ concentrations were evaluated through solution parameters, microalgal dry weight, pea growth (height, biomass), and physiological parameters, including leaf gas exchange, chlorophyll content, and normalized difference vegetation index (NDVI). Zinc accumulation in microalgal and plant biomass was also analyzed. The results revealed that microalgae increased pH and oxygen levels in the hydroponic medium while enhancing Zn accumulation in pea roots. At low ZnSO4 concentrations (2–5 mM), microalgal suspensions stimulated pea growth and photosynthetic performance. However, higher ZnSO4 levels (10–15 mM) caused Zn accumulation, leading to nutrient deficiencies and growth suppression in microalgae, which ultimately led to physiological disturbances in peas. Coelastrella sp. BGV exhibited greater tolerance to Zn stress and provided a stronger protective effect when co-cultivated with peas, highlighting its potential for phycoremediation applications.